The Students' Numerical Literacy Ability in Junior High Schools - Tampa, Alimuddin; Layly, Saadah; Helmi, Helmi; Alimuddin, Nurul Fadhila (Kreano, Jurnal Matematika Kreatif-Inovatif, 2022)
This study aims to analyze the students’ numerical literacy ability in junior high schools based on their status (accreditation and state/non-state schools). This study used the descriptive quantitative method. The participants were 150 students randomly selected from 2 state junior high schools (SMPN) based on the accreditation levels (A B) and 1 non-state school (SMP). The instrument used was the modified result of the Numerical Literacy Ability test developed by the Center for Assessment and Learning (Pusmenjar) of the Ministry of Education and Culture. The collected data were analyzed using descriptive statistics. The research results indicated that: (1) the student’s numerical literacy skills in junior high schools were low for all domains and tended to be very low in geometry; (2) at the L1 level, students did not experience difficulties, but other levels did, especially L3; and (3) school status had no significant effect on the students' numerical literacy skills.Penelitian ini bertujuan untuk menganalisis kemampuan literasi numerasi siswa di SMP berdasarkan statusnya (akreditasi dan sekolah negeri/non negeri). Penelitian ini menggunakan metode kuantitatif descriptive. Peserta tersebut merupakan 150 siswa yang dipilih secara acak dari 2 SMPN Negeri (SMPN) berdasarkan jenjang akreditasi (A/B) dan 1 sekolah non negeri (SMP). Instrumen yang digunakan merupakan hasil modifikasi dari uji Kemampuan Literasi Numerasi yang dikembangkan oleh Pusat Pengkajian dan Pembelajaran (Pusmenjar) Kementerian Pendidikan dan Kebudayaan. Data yang dikumpulkan dianalisis menggunakan statistik deskriptif. Hasil penelitian menunjukkan bahwa: (1) kemampuan literasi numerasi siswa di sekolah menengah pertama rendah untuk semua domain dan cenderung sangat rendah dalam geometri; (2) pada jenjang L1, siswa tidak mengalami kesulitan, tetapi jenjang lain mengalami kesulitan, terutama L3; dan (3) status sekolah tidak berpengaruh signifikan terhadap kemampuan literasi numerik siswa.